(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Programs in healthcare will provide important role in the diagnosis for habitually accurate early identification of cardiovascular disease. Modern data mining methods may be able to help doctors draw relevant inferences from the ever expanding amount and number of medical databases.